Cotidianidade e Serviço Social: o direcionamento ético-político e social da profissão - Brant, Nathália Lopes Caldeira (2019)
The values guiding the ethical, political, and social standards of social work, which have the professional ethical-political project as a touchstone, are expressed in everyday life, in the many social occupational spaces where this profession operates. Relying on Marx's social theory as a theoretical and methodological point of reference since the Renewal Movement in Brazil has made it possible for social work to have new signification. By looking into human life's production and reproduction, Marx developed his critique of modern society and adopts the proletarian class perspective, which determined the social and political direction of his unique contribution. The social-ontological perspective unveils the grasp of a moving totality, its determinations, and its constituent social relations. The social being (in both his objective and his subjective dimension) has labor at the fulcrum of his humanization, providing him the opportunity to fulfill his human capacities. This theoretical framework is what allowed the principles of theory and practice to change in social work, especially in scholarly production, as the profession developed. Our professional intervention takes place in the realm of everyday life, seeing as this is the privileged space where the unique aspects of social beings and social relations materialize. It is therefore critical to revisit this category and its relationship to social work, both from a critical perspective and from a professional standpoint—alternatives and possibilities included. Everyday life is characterized by heterogeneity, wherein, ultimately, everyday thinking guides the immediate actions everyday life demands. However, opening up the possibility to change everyday life and its intrinsic relationships requires a homogenizationoriented attention that is afforded only by praxis and is only possible when everyday life is suspended. In this sense, it is understood that, although expressed in everyday life, the values shaping the ethical, political, and social course of the profession must be grasped beyond everyday life, and the critical knowledge such grasp entails cannot be obtained in everyday life alone. With that in mind, using the theoretical categories of Marx's thinking, this work attempts to present a construct of his social theory, starting from the historical process, to gauge how transitory capitalist society is, considering that it hasn't always existed and will not last forever. Moreover, the study presents an analysis that goes back to the originating strands of social work, into its genesis and professionality, until its theoretical and methodological leap, following the Renovation Movement, with the adoption of Marx's social theory as a point of reference, to overcome theoretical syncretism and the conservative legacy. Challenges to expressing the ethical and moral values this professional community upholds include, on the subjective side, grasping said values and choosing among the possibilities they open up, and, on the objective side, being able to stand up for the theoretical and practical pluralism that the grasp of everyday life entails. To assert the authority of the ethical-political project, at a time when conservatism is on the rise and the meaning of the profession is being trivialized, it is imperative to stand by its values in terms of defending the working class (of which the social assistant is part) with an eye toward societal emancipation